EFEITOS DA INCLUSÃO DE ÁCIDOS GRAXOS INSATURADOS NO SUPLEMENTO DE VACAS PRIMÍPARAS ZEBUÍNAS SOBRE O DESEMPENHO PRODUTIVO E REPRODUTIVO - GODOY, Marcelo Marcondes de (2009)
Were used primiparous cows, zebuine, calved than received in the postpartum period, low intake isoenergetic supplements, in pasture of Brachiaria brizantha cv. Marandu, with twenty cows per treatment in a randomized design, where FA: the low intake supplement (LIS) with inclusion of protected fat, CO: LIS with the inclusion of meal corn and MS: only mineral supplement. Evaluated the body weight of cows (BW) of calves (BWC) and body condition score (BCS) of cows inthe postpartum period, at every 28 days, effect of sex of calf in the BW medium (BWm) and in the BCS medium (BCSm) of cows, the average daily weight gain of cows (ADWG) and calves (ADWGC) and pregnancy rate (PR). The supplementation increased the BW of the cows in FA and CO without difference between them (P> 0.05), already the MI did not differ from SM de108 to 136 days postpartum (P> 0.05). The BWC of FA and CO did not differ (P> 0.05) among them and were higher (P <0.05) than the MS 108 until 192 days postpartum, and heavier at weaning. The cows of FA had BCS higher (P <0.05) than the other treatments from 80 to 192 days postpartum. The ADWG of FA and CO did not differ among them (P> 0.05) and were higher than SM (P <0.05). The ADWGC of FA and CO were similar (P> 0.06), and higher than SM (P <0.06). Cows that nursing males had lower BWm and BCSm that those nursing females (P <0.05). The cows of FA had higher PR (P <0.01)